Job insecurity and innovative work behavior: The role of grit as a mediator - Pricilla Mourine Ham; Alice Salendu (Jurnal Ilmiah Psikologi Terapan, 2022)
The purpose of this study was to determine the role of grit as a mediator in the relationship between job insecurity and innovative work behavior in employees affected by policies due to the COVID-19 pandemic. This study is a quantitative study using an online questionnaire (Google Form) to collect data. The measuring tools used are the Innovative Work Behavior Scale, the Multidimensional Qualitative Job Insecurity Scale (MQJIS), and the Short Grit Scale (Grit-S). The participants of this study are employees in Indonesia who work in companies that implement new policies due to COVID-19. Through a nonprobability sampling technique, data were obtained for as many as 739 participants. The mediation test was carried out using the Macro PROCESS from Hayes model 4. The results showed that grit acted as a mediator in the relationship between qualitative job insecurity and innovative work behavior (B= -0.09, 95% CI [-0.13,-0.06]). Therefore, the results of this study can be used as a reference for companies to involve in measuring employee grit in the human resource management process